Nonsurfactant synthesis and characterizations of metal-organic framework MOF-5 materials using fatty alcohols - Misran H.; Othman S.Z.; Manap A.; Pauzi N.I.M.; Ramesh S. (American Scientific Publishers, 2023)
Metal-organic framework (MOF-5) nano/micro crystals materials with cubic, faceted of truncated octahedron and tetragonal morphology at ca. 0.26 ?m to 3.0 ?m were successfully synthesized using aliphatic (fatty) alcohols based sol-gel method at room temperature without further aging process. Fatty alcohols derived from palm oil with long carbon chain length of 8, 10 and 12 (i.e., octyl alcohol, decyl alcohol and dodecyl alcohol) were used during the synthesis to replace commercial surfactants. Fatty alcohols molecules was suggested to form self-assemblies at the air-water interface by surface-tension auto-oscillations and form pre-polymers that bind to the precursors where upon drying formed porous structure inside the materials. The length of carbon chains in the backbone of fatty alcohol that were used to replace the surfactant during the synthesis affected the structure of resulting MOF-5. Longer carbon chains (i.e., dodecyl alcohol) resulted in more structured framework of metal clusters and linkers with high porosity as compared to shorter template of octyl alcohol and decyl alcohol. © 2014 by American Scientific Publishers.